Waste filter cake as a catalyst source for transesterification reaction - Kumuthini, Kohilen (2025)
The utilization of industrial waste instead of disposing them offers benefits not only for waste management but also as resource recovery. This research focused on studying the heterogeneous catalytic potential of calcined waste filter cake (CFC) derived from palm empty fruit bunch (EFB) processing in the transesterification of refined palm oil (RPO) to produce biodiesel. The CFC was characterized using Scanning Electron Microscopy with Energy Dispersive X-ray Spectroscopy (SEM-EDX), Brunauer-Emmett-Teller analysis (BET) and X-ray Diffraction analysis (XRD). The results revealed a mesoporous structure (pores that are 2–50 nanometers in diameter) with a surface area of 40.88 m²/g and the predominance of crystalline calcium oxide (CaO), being the main contributions for the catalytic activity. The catalytic performance of CFC was evaluated by varying its concentrations (1.0 g, 2.0 g, 3.0 g, and 4.0 g), achieving methyl ester conversion rates of 11.51 %, 14.65 %, 25.43 %, and 23.85 %, respectively. Qualitative analysis via thin-layer chromatography (TLC) and Fourier transform infrared spectroscopy (FTIR) of the product confirmed the presence of fatty acid methyl esters (FAMEs) but revealed incomplete triglyceride conversion. Meanwhile, gas chromatography-flame ionization detection (GC-FID) analysis disclosed the quantitative data on the yield. The overall result indicated that while CFC has promising structural and chemical properties, its catalytic efficiency is limited by factors such as active site availability, limitations of mass transfer, and challenges in stirring, particularly at higher catalyst concentrations. Recommendations for enhancing CFC’s performance are to optimize calcination parameters, explore advanced reactor designs, integrate co-catalysts, and test with alternative feedstocks. Regardless of the low conversion rates, this study highlights the potential of CFC as a cost-effective, sustainable catalyst and lays the groundwork for further research to optimize its application in biodiesel production.